Arabic-English-Arabic translation : issues and strategies - Husni, Ronak; Newman, Daniel L. (Milton, Abingdon, Oxon ; New York : Routledge, 2015)
"This book is a manual for both advanced students and translators for translation between Arabic and English. The authors take a practical approach, focusing on contrastive stylistics and pay particular attention to the main areas of difficulty in English/Arabic translation. Each lesson contains translation examples and samples gleaned from authentic materials, both from literature and the media, plus additional exercises. A glossary and list of online resources are also provided at the back of the book"--
LTC-2016
includes idex.
Keywords: Arabic language -- Translating into English; Arabic language -- Foreign elements -- English; English language -- Translating into Arabic; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting